The Role of Information Seeking in Non-Fiction and Document Translation : A questionnaire survey on the information seeking habits of Finnish translators - Auranen, Karita (My University, 2025)
This thesis explores the information seeking habits of Finnish non-fiction and document translators. The aim of this study is to provide a general overview of information seeking’s role in the translation process, and how, where and for what purposes non-fiction and document translators seek information in their work. It also examines how information seeking habits have changed during translators’ careers, and what kinds of challenges they face in their work. The material for this study was collected via an online questionnaire, which was distributed to professional translators. The survey was answered by 79 Finnish non-fiction and document translators. The results highlight the importance of information seeking in translation. Information is sought online, from books and other people. A recurring motive for information seeking is terminology, which was also identified as the most common problem. Additionally, translators encounter problems related to cultural and societal differences, the commission and source text, and information seeking. The results indicate that the nature of information seeking in translators’ work continues to be shaped by the developing society and technology. More research is required on the topic to achieve a greater understanding of this central competence in translation.
Keywords: information seeking, non-fiction and document translation, Finnish translators, questionnaire survey